Incorporação de resíduo cerâmico para prevenção da retrogressão da resistência de cimentos de poços de petróleo submetidos à injeção de vapor - Souza, Pablo Diego Pinheiro de (2010)
Steam injection is the most used thermal recovery method of oil nowadays because of the high degree of development of the technique that allows high recovery factors. However, injection of superheated steam into the reservoir affects the entire structure of the well, including the cemented layer that presents a retrogression of compressive strength and increases the permeability due to formation of more crystalline and denser phases at temperatures above 110 °C. These changes result in failures in the cement that favor the entrance of formation fluids into the annulus space resulting in unsafe operations and restrictions in the economic life of the well. But the strength retrogression can be prevented by partial replacement of cement by silica-based materials that reduce the CaO/SiO2 ratio of cement slurries changing the trajectory of the reactions, converting those deleterious phases in phases with satisfactory mechanical strength and permeability. The aim of this study was to evaluate the behavior of a ceramic waste material rich in silica in partial and total substitution of a mineral additive used to fight the strength retrogression of cement slurries subjected to high temperatures. The evaluation was made by compression, X-ray diffraction (XRD) and thermogravimetry (TG/DTG). The samples were submitted to a cycle of low temperature (38 °C) for 28 days and a cycle of low temperature followed by exposure to 280 ºC and 1000 psi by 3 days. The results showed that slurries with additions of up to 30% of the waste material are not enough to prevent the strength retrogression, while slurries with additions of the waste material combined with silica flour in various proportions produced hydrated products of low Ca/Si ratios that maintained the compressive strength at satisfactory levels